P‐190: White Light Emission of Triple Core Chromophores Using Anthracene and Pyrene Moieties. Issue 1 (May 2017) - Jung, Hyocheol; Lee, Jaehyun; Shin, Hwangyu; Kim, Joonghan; Yokoyama, Daisuke; Nishimura, Hidetaka; Wakamiya, Atsushi; Park, Jongwook
Abstract : Three materials had highly twisted core structures and m‐terphenyl introduced into core. In film state, excimer emission can be interpreted as result of orientation effect. Wavelength of excimer was controlled through change of center position of triple‐core chromophore, and CIE of white light and efficiency could be controlled.